Greater skeletal contributions to leg stiffness in high compared to low-arched athletes during running and landing movements - Powell, D. W.; Paquette, M. R.; Williams, B. (ISBS Proceedings Archive (Michigan), 2017)
The contributions of skeletal and muscular structures to stiffness may underlie the distinct injury patterns observed in high- (HA) and low-arched (LA) athletes. This study compared skeletal and muscular contributions to leg stiffness in HA and LA athletes during running and landing. Ten HA and 10 LA female athletes performed five over ground running trials and five step off landing trials. Leg stiffness, and skeletal and muscular contributions to leg stiffness were calculated using Visual 3D and MatLab. HA athletes had greater leg stiffness (p=0.010) and skeletal stiffness (p=0.016) in running. During landing, HA had greater leg stiffness (p=0.015) and skeletal stiffness (p<0.001) while LA athletes had greater muscular stiffness (p=0.025). These findings demonstrate that HA athletes place a greater reliance upon skeletal structures for load attenuation during running and landing which may underlie their distinct injury patterns